2019
DOI: 10.1002/jcb.29416
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic regulation of amniotic fluid mesenchymal stem cell differentiation to the mesodermal lineages at normal and fetus‐diseased gestation

Abstract: Human mesenchymal stem cells isolated from amniotic fluid (AF‐MSCs) demonstrate the potency for self‐renewal and multidifferentiation, and can, therefore, be a potential alternative source of stem cells adapted for therapeutic purposes. The object of this study is to evaluate the efficacy of MSCs from AF when the pregnancy is normal or when the fetus is affected during pregnancy to differentiate into mesodermal lineage tissues and to elucidate epigenetic states responsible for terminal adipogenic and osteogeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 49 publications
0
10
0
Order By: Relevance
“…This result was consistent with a previous report that the suppression of DNMT1 resulted in elevating the efficiency of odontoblastic differentiation of mouse dental papilla cells [ 13 ]. In human MSCs, induction of osteogenic differentiation has been found to be associate with the decline of DNMT1 [ 29 ]. Gasiuniene et al [ 30 ] reported that osteogenic differentiation of MSCs was related to the gradual decrease in the level of DNMT1.…”
Section: Discussionmentioning
confidence: 99%
“…This result was consistent with a previous report that the suppression of DNMT1 resulted in elevating the efficiency of odontoblastic differentiation of mouse dental papilla cells [ 13 ]. In human MSCs, induction of osteogenic differentiation has been found to be associate with the decline of DNMT1 [ 29 ]. Gasiuniene et al [ 30 ] reported that osteogenic differentiation of MSCs was related to the gradual decrease in the level of DNMT1.…”
Section: Discussionmentioning
confidence: 99%
“…Aforementioned differences could possibly be explained by considering the gestational age of investigated cells, as in our study, hAFSCs were obtained from 16 to 17 weeks of normal gestations, whereas hAFSCs from polyhydramnios were obtained at 32 weeks. Although some studies, also including our previous research, showed that hAFSCs may be comparably potent in their ability to differentiate to certain lineages despite their differences in gestational age (Hamid et al, 2017;Gasiūnienė et al, 2019b;Zentelytė et al, 2020), other studies contradict this notion (Shaw et al, 2017;Huang et al, 2020). Furthermore, it is argued that pluripotent SCs typically have a lower rate of OXPHOS and maintain higher mitochondrial membrane potential in comparison to more differentiated SCs (Tsogtbaatar et al, 2020).…”
Section: Discussionmentioning
confidence: 86%
“…It should also be emphasized that scientific data about hAFSCs derived from fetus-affected gestations are very limited. Our group previously showed that hAFSCs from normal and fetus-affected gestations had similar stem cell characteristics and potential to differentiate toward mesodermal (adipogenic, osteogenic, chondrogenic, and myogenic) as well as ectodermal (neurogenic) lineages (Gasiūnienė et al, 2019b;Zentelytė et al, 2020). However, no scientific data exist on the metabolic characteristics of these two types of hAFSCs, nor are there any data on the neurogenic and neurotrophic potential of hAFSCs obtained exclusively from polyhydramnios samples.…”
Section: Introductionmentioning
confidence: 99%
“…As medical wastes, the stable cell lines of AFSCs can be obtained via amniocentesis during the pregnancy intermediate stage or cesarean section [3] . Compared with ESCs and iPSCs, the ability of AFSCs to multi-differentiate is limited, but they do not have the risk of teratoma formation [7] . In addition to these desirable properties, AFSCs participate in immunomodulation, regulate inflammation, and are universally histocompatible [8] .…”
Section: Introductionmentioning
confidence: 99%